PHYTOCHEMICAL AND TOXICITY TEST OF MERUNG EXTRACTS (Coptosapelta tomentosa (Blume) - Karolina, Anita; Pratiwi, Djihan Ryn; Akkas, Erwin (Jurusan Kimia FMIPA UNMUL, 2018)
This study was conducted to determine the content of secondary metabolites and the toxicity of extracts of Merung various parts (Coptosapelta tomentosa (Blume). The research methods included maceration, phytochemical tests and toxicity tests using the BSLT method. Based on the results of the phytochemical test showed all extracts of Merung parts contained steroids, flavonoids, and phenolics. Saponin is only found in leaf extract. Toxicity tests using the BSLT method showed that stem and root extracts were toxic with LC50 values of 2004.06 and 173.09 ppm, respectively.